Involvement of CircRNA Expression Profile in Diabetic Retinopathy and Its Potential Diagnostic Value - He, Hengqian; Zhang, Juntao; Gong, Weikun; Liu, Mengyun; Liu, Hao; Li, Xiaoyong; Wu, Yufei; Lu, Qinkang (Frontiers in Genetics, 2022)
Background: Circular RNAs (circRNAs), a class of non-coding and undegradable RNAs, play many pathological functions by acting as miRNA sponges, interacting with RNA-binding proteins, and others. The recent literature indicates that circRNAs possess the advanced superiority for the early screening of diabetic retinopathy (DR). Methods: CircRNA sources of peripheral blood mononuclear cells (PBMCs) from healthy controls (n = 4), diabetes mellitus patients (DM) (n = 4), and DR patients (n = 4) were extracted for circular RNA microarray analysis. Enriched biological modules and signaling pathways were analyzed by Gene Ontology Enrichment and Kyoto Encyclopedia of Genes and Genomes analysis, respectively. Real-time quantitative reverse transcription PCR (RT-qPCR) was performed to validate differentiated levels of several circRNAs (fold change ≥2, p < .05) in different groups of healthy control subjects (n = 20), DM patients (n = 60), and DR patients (n = 42). Based on our clinical data from DR, the diagnostic performance of candidate circRNAs was measured by operating characteristic curves (ROCs). Subsequently, their circRNA–miRNA networks were constructed by bioinformatics analysis. Results: Circular RNA microarray analysis was performed, and 2,452 and 289 circRNAs were screened with differential expression in DR patients compared to healthy controls and DM patients, respectively. Enrichment analyses showed that circRNAs in DR patients were enriched in extracellular matrix (ECM)–receptor interaction and focal adhesion pathways. The top 5 differential circRNAs in circRNA microarray analysis were subsequently quantified and verified by RT-qPCR. Consistently, a significant 2.2-fold reduction of hsa_circ_0095008 and 1.7-fold increase in hsa_circ_0001883 were identified in DR patients compared to DM patients. Meanwhile, the area under curves of hsa_circ_0095008 and hsa_circ_0001883 were 0.6710 (95% CI, 0.5646–0.7775) (p = 0.003399) and 0.6071 (95% CI, 0.4953–0.7189) (p = 0.06644), respectively, indicating a good diagnostic value. Conclusion: Our study provided a new sight for the pathological mechanism of DR and revealed the potential value of hsa_circ_0095008 and hsa_circ_0001883 as diagnostic biomarkers for the early diagnosis of DR patients.